KEEFEKTIFAN MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN MENULIS SISWA KELAS VIII SMP NEGERI 33 MAKASSAR - Akram Budiman Yusuf (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2017)
This study aims to test the effectiveness of project-based learning model on the ability to write poetry students of class VIII SMP Negeri 33 Makassar. The data of this research are obtained from the value of learning result before the treatment (pre-test) to know the ability of student poetry writing and postes score to know the poem ability of the students based on the conformity of the content with theme, image, diction, figurative language / language style and typography with using a project-based learning model. The result of pretest data analysis is known that the ability to write poetry is not enough yet because the number of students who score 70 and above has not reached 85% and the ability to write posttest poem is adequate because the number of students who scored 70 upward has reached 85%. The result of inferential analysis also shows that the normalized gain average appears that the sig value. (2-tailed) is 0,000 which is 0.000 0.05 so it can be concluded that H0 is rejected and H1 is accepted which means that the average increase in student learning outcomes ≥ 30. In addition the results of inferential statistical analysis also indicate that students' which is performed by using a proportion test with a significant level of 5% obtained Z table = 1.64 where H0 accepted if Z arithmetic ≤ 1.64. Because the value of Z arithmetic is 2.017, H1 is accepted and H0 is rejected, which means student completeness in classical ≥ 85%. So it can be concluded that the use of project-based learning model on the ability of writing poetry meet the criteria effectively.